The double-jack murders - McManus, Patrick F. (McManus, Patrick F. Sheriff Bo Tully mystery., 2009)
While leading a would-be killer into the open, Sheriff Bo Tully also pursues a seventy-five-year-old missing persons case in which a pair of gold miners (a two-man drilling team known as a double-jack) mysteriously disappeared just as they hit the mother lode in a remote part of Blight County.